2008
DOI: 10.1111/j.1365-2672.2007.03593.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Bifidobacterium longum prevents gut-derived Pseudomonas aeruginosa sepsis in mice

Abstract: Aims:  The aim of the study was to evaluate the efficacy of probiotics on gut‐derived sepsis caused by Pseudomonas aeruginosa in immunocompromised mice. Methods and Results:  After oral inoculation of P. aeruginosa, mice were treated with cyclophosphamide to induce leucopenia and translocation of the intestinal P. aeruginosa into blood, thereby producing gut‐derived sepsis. In this model, administration of 1 × 109 CFU of Bifidobacterium longum strain BB536 for 10 days significantly (P < 0·01) increased the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 31 publications
2
39
1
1
Order By: Relevance
“…Although some of the studies (Lin et al, 2005;Matsumoto et al, 2008;Stoll and Hansen, 2008) predicated that probiotics may reduce the incidence of sepsis; literature did not confirm this association (Schanler, 2006;Deshpande et al, 2007). Our study did not show that L. sporogenes reduced the incidence of sepsis in VLBW infants.…”
Section: Discussioncontrasting
confidence: 46%
“…Although some of the studies (Lin et al, 2005;Matsumoto et al, 2008;Stoll and Hansen, 2008) predicated that probiotics may reduce the incidence of sepsis; literature did not confirm this association (Schanler, 2006;Deshpande et al, 2007). Our study did not show that L. sporogenes reduced the incidence of sepsis in VLBW infants.…”
Section: Discussioncontrasting
confidence: 46%
“…Several studies have reported that probiotic bacteria can adhere to intestinal epithelial cells and can competitively inhibit adhesion and invasion by enteric pathogens. 3,4,20,23) Moreover, heat-killed probiotic bacteria retain the ability to bind to cultured Int-407 and Caco-2 cells as well as viable probiotic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Bifidobacterium protected E. coli O157 infection in germ-free mice (26). Oral administration of Bifidobacterium longum prevented P. aeruginosa gut-derived sepsis in a mouse model (27). Heat-killed L. casei protected against P. aeruginosa infection in mice (28).…”
Section: Acquisition Of Tolerance To Bacterial Infection By Ingestingmentioning
confidence: 99%